Epidemiological profile of Brain Death notifications (Research, Society and Development, 2020)
Objective: to analyze the epidemiological profile of brain death notifications. Method: this is a retrospective, analytical and descriptive study with a quantitative approach, carried out through the analysis of medical records and forms for opening the Brain Death protocol, identifying its sociodemographic, clinical aspects and aspects of the organ and tissue donation process. Result: there was a prevalence of males, with a mean age of 37.34 years. Regarding the cause of the coma, stroke presented a higher percentage, with subarachnoid hemorrhage as the most prevalent diagnosis. Transcranial doppler was the most widely used confirmatory test. When it comes to the effectiveness of the donation, it was observed that a higher percentage of non-donors, presenting logistical / structural / other problems as the main causes. Conclusion: it was identified the need to carry out continuing education to improve the records of health professionals in the medical records, the importance of sensitizing the population about the process of organ and tissue donation and updates of professionals in relation to the methods of maintaining the potential donor.